Recent Security Solutions For VANET Communications: A Systematic Review - et. al., Megha V Kadam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
- In wireless network which is now widely deployed in urban areas for intelligent transport system (ITS) called Vehicular Ad Hoc Networks (VANETs). Due to the open nature of VANETs, they are vulnerable to various security threats as such networks are mainly depends on control, communication and computing technologies. The fault or malicious vehicles in VANET may lead to serious accidents and public assets lost due to miscommunications based on vehicle sensor data. Therefore, if the detection of such sensor data is not effectively handled then it may lead to traffic jams, road accidents, etc as most of the vehicles wrongly redirected by face traffic alerts. Thus providing reliable communications among the V2V or V2I is the first research problem. There are different security solutions presented to achieve the efficient an reliable VANET communications under the domain of cryptography, trust-based, and hybrd. The aim of this paper is to take the review such recent works for network security. The outcome of this paper claims the various research gaps identified from the literature review.